2012
DOI: 10.1007/s11010-012-1430-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 protects rat PC12 pheochromocytoma cells from serum deprivation-induced cell death

Abstract: Interleukin-22 , an IL-10 family cytokine, mediates the crosstalk between leukocytes and epithelial cells. Previous studies reported that IL-22 expresses in mouse brain, and the rat PC12 cells are responsive to IL-22 stimulation. However, the biological roles of IL-22 in neuronal cells remain largely unknown. We show here that IL-22 activates Stat3, p38 mitogen-activated protein kinases (MAPK), and Akt pathways and inhibits Erk/MAPK pathway in naïve PC12 cells. We further demonstrate that IL-22 protects naïve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…This effect was mediated, at least in part, by a decrease of apoptosis. Supporting these findings, previous studies have shown that IL-22-treated rat pheochromocytoma cells exhibit a modest increased survival in serum-deprived conditions [ 59 ]. Some authors have found that IL-22 increased the proliferative function of keratinocytes [ 19 , 60 ] or colonic epithelial cells [ 42 ].…”
Section: Discussionsupporting
confidence: 68%
“…This effect was mediated, at least in part, by a decrease of apoptosis. Supporting these findings, previous studies have shown that IL-22-treated rat pheochromocytoma cells exhibit a modest increased survival in serum-deprived conditions [ 59 ]. Some authors have found that IL-22 increased the proliferative function of keratinocytes [ 19 , 60 ] or colonic epithelial cells [ 42 ].…”
Section: Discussionsupporting
confidence: 68%
“…Our results demonstrate that the overexpression of Kv1.5 didn't significant inhibited survival after MPP + treatment in PC12, Kv1.5 gene knockdown was more sensitive for MPP + . Previously, accumulating evidence suggested that activation of the PI3K/Akt pathway inhibited MPP + induced PC12 apoptosis [28,29]. The salient feature of the data presented in this report was the finding that Kv1.5 involved in MPP + induced neurotoxicity.…”
Section: Discussionsupporting
confidence: 49%
“…In the case of IL22 , its expression was strongly induced by PACAP38 treatment at 24 h in both the ischemic and healthy penumbras but that was especially high in the ischemic penumbra. Although not much is known about the biological role of this cytokine in neuronal cells, a recent study using naïve PC12 cells suggested a role for IL22 in neurological processes, a first such report showing a neuroprotective function for this cytokine [ 31 ]. Another unrelated work on lung infection by the influenza A virus showed that IL22 limits lung inflammation and subsequent bacterial superinfections [ 32 ].…”
Section: Discussionmentioning
confidence: 99%